Friday

April 18, 2014

April 18, 2014

Posted by **thully ntuli** on Tuesday, February 5, 2013 at 8:42am.

- maths science -
**Steve**, Tuesday, February 5, 2013 at 10:16am3a+b+5a+2b = 3a+5a + b+2b = 8a+3b

4(e-2)-2(e+1) = 4e-8-2e-2 = 2e-10

if y(x) = (2x+1)(x-2)

y(-2) = (2(-2)+1)(-2-2) = (-4+1)(-4) = 12

**Related Questions**

Pre-Calc-please check - Please check this for me expand (3z-2b)^5 using Binomial...

maths - (Q1)a+3b+2c=3,2a-b-3c=-8,5a+2b+c=9.solve for a,b&c by matrix method. (a)...

alg - Find the sum. Express your answer in simplest form. (14a^2 / 2b) + (3a / ...

Math - Find the HCF 1) 7x and 9 : nothing 2) x^2(x-4) and x(x-4) : its (x-4)? 3...

Algebra 1b! - 1. Find the excluded value of x for the polynomomial expression ...

math binomial expansion - binomial expansion (3a^2-2b^3)^4 is this right? (3a^2...

algebra - 1 Solve the set of linear equations by the matrix method : a+3b+2c=3...

algebra - Is this correct? subtract (4a^3+2b^3)-(6a^3+5a^2b-2ab^2+2b^3) answer...

Math(Please Check My Work.) - 3a^3b^2(-a^3b-a^2b^2)=-3a^9b^3-3a^6b^4 *is this ...

algebra 2 - 5a-b=17 3a+2b=5